(untitled) (Malaysian Journal of Civil Engineering, 2018)
Palm oil clinker (POC) is a waste from the incineration of palm oil shell and fibre. It can be easily obtained from palm oil mill and is abundant available resources. This paper focused on characterization of POC used as fine and coarse aggregates in concrete. The utilization of POC has been accepted to produce lightweight concrete, apart from overcoming the POC disposal problems. Moreover, the use of POC in concrete also could overcome the depletion of sand and granite which can cause nature imbalance. In this study, the characterization of aggregates covers the physical and strength properties. In order to obtain the physical properties, the specific gravity, water absorption, sieve analysis, fineness modulus and moisture content tests were conducted. For strength properties, Los Angeles abrasion value test was conducted. It was found that the coarse and fine POC aggregates have a density of 817.17 kg/m3 and 917.82 kg/m3 , respectively, which were lighter than normal granite and sand as much as 36.85%% and 29.45%. This is due to its porous nature of POC aggregates. This nature tends to absorb excessive water which contributes to higher moisture content and water absorption. This study concludes that POC aggregates have a potential in producing lightweight aggregate for concrete.